Probabilistic assessment of aviation CO2 emission targets. (August 2018) - Hassan, Mohammed; Pfaender, Holger; Mavris, Dimitri
Highlights: Regulatory bodies set environmental targets for the aviation industry. Technologies, operations and biofuels are to enable achieving those targets. A partial equilibrium model is developed to quantify expected performance. Monte Carlo simulations are conducted to account for uncertainty. Biofuels are found to be essential if targets are to be met. Abstract: Passenger demand for air transportation is expected to continue growing into the future. The increase in operations will undoubtedly lead to an escalation in harmful carbon dioxide emissions, an adverse effect that governing bodies have been striving to mitigate. The International Air Transport Association has set aggressive environmental targets for the global aviation industry. This paper investigates the achievability of those targets in the US using a top-down partial equilibrium model of the aviation system complemented with a previously developed fleet turnover procedure. Three 'enablers' are considered: aircraft technologies, operational improvements and sustainable biofuels. To account for sources of uncertainty, Monte Carlo simulations are conducted to run a multitude of scenarios. It was found that the likelihood of meeting all targets is extremely low (0.3%) for the expected demand growth rates in the US. Results show that biofuels have the most impact on system CO2 emissions, responsible for an average 64% of the total savings by 2050 (with aircraft technologies and operational improvements responsible for 31% and 5%, respectively). However, this impact is associated with high uncertainty and very dependent on both biofuel type and availability.